ANALISIS SENTIMEN REVIEW WISATAWAN PADA OBJEK WISATA UBUD MENGGUNAKAN ALGORITMA SUPPORT VECTOR MACHINE - I Wayan Budi Suryawan; Nengah Widya Utami; Ketut Queena Fredlina (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Since the world was hit by the Covid-19 pandemic, it had an impact on activities in Ubud. According to the Central Bureau of Statistics from Bali, the number of foreign tourists visiting from January to October 2021 has decreased by 99.996 percent. On October 14 2021 tourist attractions in Ubud began to reopen. Based on these problems, this research will carry out sentiment analysis from reviews on the TripAdvisor site on tourist attractions in Ubud using the Support Vector Machine algorithm with the Knowledge Discovery in Database method. The results obtained in this study resulted in 551 positive sentiment and 118 negative sentiment based on 669 data test, these results resulted in a positive value for tourist attractions in Ubud. Testing will be carried out on the Support Vector Machine algorithm using the Confusion Matrix which gets good results in conducting sentiment analysis with an accuracy of 84.01%, a recall of 89.83%, a precision of 90.40% and an F1-Score of 90. 11%.